The content and composition of organic matter in bottom sediments of the Rybnik reservoir - preliminary studies - Baran, Agnieszka; Mierzwa-Hersztek, Monika; Gondek, Krzysztof; Szara, Magdalena; Tarnawski, Marek (Geology, Geophysics and Environment, 2018)
Organic matter has important influences on the fate of environmental pollution in water dam reservoirs. The aim of the studies was to assess content of organic matter fractions in Rybnik reservoir bottom sediments, and to determine their influence on the content of heavy metals and PAHs. In three sediment samples, the content of C organic (Corg), C extracted (Cex), C humic acid (Cha), C fulvic acid (Cfa) and C non-hydrolyzed (Cnh), buffer capacity, and content of heavy metals and PAHs was analyzed. We found the highest content of Corg, Cex, Cha, Cfa and Cnh in sample 3 (the outlet, near the dam), while the lowest content was found in sample 2 (middle). The fraction of Cnh was dominant in sediment sample 3 (outlet, near dam) and 1 (inlet), whereas the fraction of Cha dominated in sample 2 (middle). Rybnik bottom sediments are characterized by their high buffer capacities (samples 3, 1) shaped among others by the high content of organic matter. The high organic matter content in samples 3 (outlet) and 1 (inlet) and also high total contents of heavy metals and PAHS in these sediments demonstrate that these pollutants have a strong affinity for organic matter in the sediments. Moreover, the highest mobility of metals, from sample 2 (middle), is connected with the low content of organic matter substances and the low buffer capacities of sediments.